1983
DOI: 10.2134/agronj1983.00021962007500030030x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Yield of Kentucky Bluegrass as Affected by Post‐Harvest Residue Removal1

Abstract: Field burning of post‐harvest residue has been an established management practice for economical production of Kentucky bluegrass (Poa pratensis L.) seed. Fields not burned soon after harvest usually have poor seed production in the following year. Residue remaining on fields shades, and thereby restricts tiller growth and subsequent seed yield. To explore the hypothesis, polyethylene shade screens which excluded 30 and 67% of sunlight were placed over September field‐burned ‘Baron’ Kentucky bluegrass plants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…Chilcote et al (1974) reported that fall tiller regrowth of creeping red fescue was shorter when straw and stubble were removed by burning. Similar results have been reported in Kentucky bluegrass (Hickey and Ensign, 1983; Ensign et al, 1983). The regrowth height of fall tillers has been shown to be negatively correlated with flowering and yield potential in Kentucky bluegrass (Chastain et al, 1997).…”
Section: Discussionsupporting
confidence: 89%
“…Chilcote et al (1974) reported that fall tiller regrowth of creeping red fescue was shorter when straw and stubble were removed by burning. Similar results have been reported in Kentucky bluegrass (Hickey and Ensign, 1983; Ensign et al, 1983). The regrowth height of fall tillers has been shown to be negatively correlated with flowering and yield potential in Kentucky bluegrass (Chastain et al, 1997).…”
Section: Discussionsupporting
confidence: 89%
“…The first seed crop is usually harvested 14 to 15 mo after planting, and is produced without prior post‐harvest residue management. Following harvest of the first and subsequent seed crops, post‐harvest residue must be removed from Kentucky bluegrass fields to maintain future seed yields (Ensign et al, 1978) Where post‐harvest residue remained on grass fields, seed yields declined as much as 80%, compared with seed production with open‐field burning (Canode and Law, 1977)…”
mentioning
confidence: 99%
“…Idaho and Oregon placed restrictions on when, where, and the amount of acreage that can be burned daily based on meteorological models that predict when the atmospheric wind current will best disperse the smoke away from population centers. Several studies evaluated alternatives to burning, but none were as effective as burning in maintaining productive stands and seed yields (5,7). Removing at least 90% of the post-harvest residue maintained stand productivity (seed yield) in non-burn production systems for the first three years of production, but after three years the non-burning residue removal method yielded less than burning (4,5).…”
Section: Introductionmentioning
confidence: 99%